sosial Dominasi Aktor Sosial dalam Berita Tagar.ID Berjudul Applikasi Injil Berbahasa Minangkabau - Firdaus, Saiyidinal (Universitas Putera Batam, 2022)
This study aims to describe the dominance of social actor contained in the Tagar. Id's Minangkabau language Gospel application news. The researcher uses van Dijk's view in showing the relationship between social cognition and social actor in mass media's news. The researcher also uses Fairclough's socio-cultural approach in offering the relationship of discourse observed and socio-cultural perspective in the report. Thus, the researcher applies a qualitative approach with van Dijk's socio-cognitive and Fairclough's socio-cultural approach as an analytical knife. The study result indicates the person scheme and event scheme domination in the Tagar. Id's Minangkabau language Gospel application news. The two schemes play an essential role in describing Irwan Prayitno's figure as West Sumatera Governor through the Minangkabau socio-cultural reality. In van Dijk's point of view, social cognition is a form of effort in examining an event or events based on the characters' involvement in the news text. The figure of Irwan Prayitno as the governor of West Sumatra becomes a particular interpretation process for Tagar. Id journalist in producing news by analyzing the leadership form of Irwan Prayitno and the event that happened in Minangkabau community as details of Irwan Prayitno's profile, the socio-cultural reality of the Minangkabau community, and the reasons for rejecting the Minangkabau language Gospel application.